2014
DOI: 10.5935/0101-2800.20140040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical training and potassium supplementation on blood pressure, glucose metabolism and albuminuria of spontaneously hypertensive rats

Abstract: Efeito do exercício físico e suplementação de potássio sobre a pressão arterial, metabolismo glicídico e albuminúria de ratos hipertensosEffects of physical training and potassium supplementation on blood pressure, glucose metabolism and albuminuria of spontaneously hypertensive rats Introdução: Ainda é controverso se ocorre sinergismo entre as diferentes medidas não farmacológicas utilizadas no tratamento da hipertensão arterial. Objetivo: Avaliar o efeito do exercício físico aeróbico, da sobrecarga oral de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Phosphorus-free mineral mix (AIN-93G mix without phosphorus) and potassium phosphate from Dyets Inc. were used to modify the phosphorus content of the diet. Potassium phosphate was used because the addition of potassium does not affect growth ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorus-free mineral mix (AIN-93G mix without phosphorus) and potassium phosphate from Dyets Inc. were used to modify the phosphorus content of the diet. Potassium phosphate was used because the addition of potassium does not affect growth ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have shown that obesity and ET exercise training presented inverse effects on glucose metabolism, hormonal levels, blood pressure, and lipid profile (Relling et al 2006;Haram et al 2009;Leopoldo et al 2010;Leopoldo et al 2011;Caponi et al 2012;Jodas et al 2014;Lima-Leopoldo et al 2014;Garcia et al 2016). While ET generates beneficial responses on metabolism as improvements in insulin sensitivity, hypertension reduction, and metabolic control (Haram et al 2009;Jodas et al 2014), obesity promotes metabolic disorders such as glucose intolerance, insulin resistance, hypertension, and dyslipidemia (Relling et al 2006;Leopoldo et al 2010;Leopoldo et al 2011;Lima-Leopoldo et al 2011) in rodents, resemble the metabolic syndrome ascertained in humans. According Haram et al (2009), the exercise training is important to correct abnormalities in insulin action and metabolic parameters, being these advantages potentiated by increasing the intensity of activity.…”
Section: Discussionmentioning
confidence: 98%
“…It is well recognized that water and electrolyte homeostasis, namely the transport and excretion of sodium, potassium and chloride, were closely related to renal function (Wirz and Geigy, 1961; Gavras et al, 1976). Previous researches indicated that potassium supplementation effectively ameliorated high blood pressure and renal injury in SHR (Galdino et al, 2010; Jodas et al, 2014). The results in our present study demonstrated long-term intake of PASE increased the serum levels of K+.…”
Section: Discussionmentioning
confidence: 99%